Neuroprotective effects of levetiracetam target xCT in astrocytes in parkinsonian mice. Issue 1 (10th November 2015) - Miyazaki, Ikuko; Murakami, Shinki; Torigoe, Nao; Kitamura, Yoshihisa; Asanuma, Masato
Abstract: Astrocytes but not neurons express cystine/glutamate exchange transporter (xCT), which takes up cystine, and consequently supplies the substrate for GSH synthesis in neurons. It is recognized that GSH synthesis in neurons is dependent on the expression of xCT in astrocytes. Previous studies reported that levetiracetam (LEV), an anti‐epileptic drug, increased xCT expression in vivo . The purpose of this study was to examine neuroprotective effects of LEV in parkinsonian models and demonstrate xCT in astrocytes as a target of neuroprotection against dopaminergic neurodegeneration. We identified striatal astrocytes cultured with LEV showed significant increase in xCT expression and GSH levels. Preincubation of primary cultured mesencephalic dopamine neurons with conditioned media from LEV‐treated astrocytes protected against 6‐hydroxydopamine (6‐OHDA)‐induced neurotoxicity. These protective effects were canceled by xCT inhibitor. Furthermore, reduction of nigrostriatal dopaminergic neurons in 6‐OHDA‐lesioned parkinsonian mice was significantly abrogated by repeated injections of LEV. Treatment with LEV significantly increased the expression of xCT in striatal astrocytes in the hemi‐parkinsonian mice. In conclusion, LEV exerts neuroprotective effects against neurodegeneration via up‐regulation of xCT and GSH in astrocytes. Thus, xCT in astrocytes could be a potential target in novel neuroprotective approaches to prevent degeneration of dopaminergic neurons. Glutathione (GSH) is the most potent intrinsic antioxidant. Since extracellular cysteine is readily oxidized to form cystine, cystine transport mechanisms are essential to provide cells with cysteine. Cystine uptake is mediated by cystine/glutamate exchange transporter (xCT), expressed primarily on astrocytes, but not on neurons. Astrocytes take up cystine via xCT and reduce it to cysteine to supply cysteine, the substrate for GSH synthesis in neurons. This study demonstrated that levetiracetam (LEV), an anti‐epileptic drug, increased GSH in/from astrocytes via xCT up‐regulation. GSH derived from astrocytes protects dopamine neurons against neurotoxicity induced by dopaminergic neurotoxin 6‐hydroxydopamine (6‐OHDA). Thus, xCT in astrocytes could be a potential target in novel neuroprotective approaches to prevent degeneration of dopaminergic neurons. Abstract : Glutathione (GSH) is the most potent intrinsic antioxidant. Since extracellular cysteine is readily oxidized to form cystine, cystine transport mechanisms are essential to provide cells with cysteine. Cystine uptake is mediated by cystine/glutamate exchange transporter (xCT), expressed primarily on astrocytes, but not on neurons. Astrocytes take up cystine via xCT and reduce it to cysteine to supply cysteine, the substrate for GSH synthesis in neurons. This study demonstrated that levetiracetam (LEV), an anti‐epileptic drug, increased GSH in/from astrocytes via xCT up‐regulation. GSH derived from astrocytes protects dopamine neurons against neurotoxicity induced by dopaminergic neurotoxin 6‐hydroxydopamine (6‐OHDA). Thus, xCT in astrocytes could be a potential target in novel neuroprotective approaches to prevent degeneration of dopaminergic neurons.